Spirit of the Delta : The Art of Carolyn Norris - Shawhan, Dorothy (Book collections on Project MUSE., 2011)
Raised in West Virginia, self-taught artist Carolyn Norris (b. 1948) moved as a young woman of twenty-one to Cleveland, Mississippi, a quintessential Delta railroad town on the famous blues Highway 61. To create one of her first paintings, she tore the wooden back off a dresser to use as a canvas. She painted with available house paint and completed the painting with face makeup. Thus began the realization of a passionate need to paint. Eventually, Norris came to serve as the visual griot of Cleveland. She has used a variety of media, painting on canvas, wood, paper, cardboard, glass, plates.